Motor Stereotypies: A Pathophysiological Review - Péter, Zsanett; Oliphant, Melody E.; Fernandez, Thomas V. (Frontiers in Neuroscience, 2017)
Motor stereotypies are common, repetitive, rhythmic movements with typical onset in early childhood. While most often described in children with autism spectrum disorder and intellectual disability, stereotypies can also present without developmental delay and persist into adulthood. Stereotypies are often disruptive and harmful, both physically and socially, and effective evidence-based treatments are lacking. This can be attributed, in part, to our incomplete knowledge of the underlying biological and environmental risk. Several studies implicate various neurotransmitters, brain circuits, anatomical loci, and pre- and postnatal environmental influences in stereotypy onset and symptom severity. However, there are few points of convergence among a relatively small number of studies, indicating that more research is needed to confirm the underlying bases of risk. Of particular note is the lack of published genetic studies of stereotypies, despite evidence for Mendelian inheritance patterns in some families. Focusing future studies on typically-developing children with primary motor stereotypies may be a useful approach to minimize potential biological, environmental, and genetic heterogeneity that could theoretically hinder consistent findings. Ultimately, a deeper understanding of the underlying biology and risk factors for motor stereotypies will lead us closer to more effective targeted therapies that will alleviate suffering in affected children.